Keeping the Promise of Social Security in Latin America - Gill, Indermit S. (Palo Alto, CA: Stanford University Press, 2012)
Nations around the world (both large and small, rich and poor) are engaged in debate over how to reform their social security systems and care for the aged. For many countries this debate requires speculation on hypothetical scenarios, but in Latin America a rich body of experience on social security reform has been accumulating for more than a decade (for Chile, more than two decades). This report, entitled, Keeping the Promise of Social Security in Latin America, takes stock of those reforms, evaluates their successes and failures, and considers the lessons that can be drawn for the future of pension policy in the region. The authors draw on a series of background papers and surveys commissioned specifically for this inquiry, as well as existing research conducted by themselves and other pension experts. In the debate on pension reform there is no orthodoxy, as reflected in major differences of opinion among leading experts. Despite more than a decade of experience with pension reform in Latin America, although undoubtedly a major step forward, reforms are still works in progress. This report furthers enrich the policy dialogue that is of crucial importance to the future of the region.